Peritonitis of pyelorenal origin - Perdomo, Roberto (Cirugía del Uruguay, 2020)
Five cases of peritonitis of pyelorenal origin are reported upon. Four of them were of the spontaneous type undergoing unspecific pyelonephritis and pyonephrosis, consistent a;ssociated with pyelocalicial dilation and, in two instances, with lithiasis. A discussion is carried out of the etiologic and pathologic fe,atures, as well as of those related with the clinical and operative diagnosis and with emergency therapy. Stress is laid on the fact that positive diagnosis is essential in the adequate planning of surgical treatment.